CNS Irradiation Effects on Puberty and Growth - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The relation between age at irradiation, sex, and age at puberty onset was determined in 36 children treated with high-dose irradiation for tumors anatomically distant from the hypothalamic-pituitary region at the New York University Medical Center, St Luke's/Roosevelt Hospital, and Memorial Sloan Kettering Cancer Center, New York.